Methotrexate, Cyclosporine A, and Biologics Protect against Atherosclerosis in Rheumatoid Arthritis - Bartłomiej Kisiel; Robert Kruszewski; Aleksandra Juszkiewicz; Anna Raczkiewicz; Artur Bachta; Małgorzata Tłustochowicz; Jadwiga Staniszewska-Varga; Krzysztof Kłos; Krzysztof Duda; Romana Bogusławska-Walecka; Rafał Płoski; Witold Tłustochowicz (Journal of Immunology Research)
Introduction. The risk of cardiovascular disease is increased in rheumatoid arthritis (RA). A meta-analysis showed increased intima media thickness (IMT) in RA. It has been shown that disease modifying antirheumatic drugs (DMARDs) may influence the progression of atherosclerosis. However, it was suggested that biologics may be more efficient than other DMARDs (including methotrexate—MTX) in protecting against atherosclerosis. Objectives. The aim of this study was to assess the influence of different RA characteristics and treatment regimens on IMT and atherosclerotic plaques. Patients and Methods. 317 RA patients and 111 controls were included in the study. IMT was measured in carotid (CIMT) and femoral (FIMT) arteries. Arteries were screened for the presence of plaques. Results. CIMT, FIMT, and prevalence of plaques were lower in patients treated with methotrexate (MTX) ≥ 20 mg/wk, cyclosporine (CsA), or biologics than in patients treated with lower doses of MTX and other disease modifying antirheumatic drugs. No differences in IMT between patients treated with MTX ≥ 20 mg/wk, biologics, or CsA were found. Conclusions. We found a beneficial effect of MTX ≥ 20 mg/wk, biologics, and CsA on atherosclerosis. We do not confirm a stronger influence of biologics on IMT compared with therapeutic doses of MTX.